(untitled) (Sudurpaschim Spectrum, 2024)
Customer perception encompasses how individuals select, organize, and interpret information to form a coherent understanding of a brand or service. This study examines customer perceptions regarding the service delivery of finance companies in Mahendranagar. The primary objectives are to evaluate the impact of security, analyze employee behavior, assess the role of trust and reliability, and determine the effect of accessibility on customer perceptions. The research involved 140 participants from diverse professional backgrounds, using a 24-item questionnaire. Data were collected through convenience sampling, ensuring representation across different genders, ages, and occupations. The study highlighted four critical aspects of financial service delivery— accessibility, trust and reliability, employee behavior, and security—that significantly shape customer perceptions. These service quality dimensions are essential in influencing customer satisfaction. The findings suggest that trust and reliability exert the most considerable effect on customer perceptions compared to other factors. This research provides valuable insights for finance companies in Mahendranagar, offering guidance on improving service delivery by focusing on these key factors to enhance customer satisfaction and loyalty.